When boosting gender stereotypes increases flow experience and reduces self-handicapping in gamified tutoring systems - do Nascimento, João Vitor Lourenço Batista; dos Santos Júnior, Jário José; Challco, Geiser Chalco; Bittencourt, Ig Ibert (Journal of the Brazilian Computer Society, 2024)
The threat of stereotypes affects various psychological mechanisms, including affective/subjective, cognitive, and motivational ones, and can be present in gamified online educational environments in various ways. In this study, we aimed to investigate whether gender stereotypes in gamified virtual environments could affect the flow experience, self-handicapping behavior, and performance of Brazilian students. To achieve this, we experimented with 147 participants (60 males and 87 females) who were high school and higher education students from public and private institutions in the state of Alagoas, located in the northeastern region of Brazil. We randomly allocated the participants to three distinct virtual environments: a neutral environment, a male-stereotyped environment, and a female-stereotyped environment. We introduced the stereotype threat condition when the participant was in an environment that did not correspond to their gender. In contrast, the boost condition occurred when the environment corresponded to their gender. The results of this study indicate that the presence of gender stereotypes can influence both the flow experience and the self-handicapping behavior of Brazilian students in gamified virtual environments. We observed statistically significant differences that suggest that the implementation of stereotypes can influence the relationship between variables.